Assessing the non-inferiority of prosthesis constructs used in hip replacement using data from the National Joint Registry of England, Wales, Northern Ireland and the Isle of Man: a benchmarking study. Issue 4 (29th April 2019) - Deere, Kevin C; Whitehouse, Michael R; Porter, Martyn; Blom, Ashley W; Sayers, Adrian
Abstract : Objectives: To investigate the relative performance of hip prosthesis constructs as compared with the best performing prosthesis constructs and illustrate the substantial variability in performance of currently used prostheses. Design: A non-inferiority study. Setting: The National Joint Registry for England, Wales, Northern Ireland and the Isle of Man (NJR). Participants: All patients with a primary total hip replacement registered in the NJR between 1 April 2003 and 31 December 2016. Main outcome measures: Kaplan-Meier failure function for hip prosthesis constructs. Failure difference between best performing construct and remaining constructs. Methods: Using a non-inferiority analysis, the performance of hip prosthesis constructs by brand were compared with the best performing contemporary construct. Construct failure was estimated using the 1-Kaplan-Meier survival function method, that is, an estimate of net failure. The difference in failure between the contemporary benchmark and all other constructs was tested. Results: Of the 4442 constructs used, only 134 had ≥500 procedures at risk at 3 years postprimary, 89 of which were not demonstrated to be inferior to the benchmark by at least 100% relative risk. By 10 years postprimary, there were 26 constructs with ≥500 at risk, 13 of which were not demonstrated to be inferior by at least 20% relative risk. Even fewer constructs were not inferior to the benchmark when analysed by age and gender. At 5 years postprimary, there were 15 constructs in males and 11 in females, aged 55–75 years, not shown to be inferior. Conclusions: There is great variability in construct performance and the majority of constructs have not been demonstrated to be non-inferior to contemporary benchmarks. These results can help to inform patients, clinicians and commissioners when considering hip replacement surgery.